Evaluation of Pencak Silat Extracurricular Management for SMP Negeri 19 and SMP Negeri 32 during the Covid-19 Pandemic in Surabaya City - Moh. Rizal Charbi; Purbodjati Purbodjati; Advendi Kristiyandaru (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The purpose of this study was to determine the strengths, weaknesses, opportunities, and threats of Pencak silat extracurricular management which includes Planning, Organizing, Implementation, and Supervision of SMP Negeri 19 and SMP Negeri 32 in Surabaya. The approach used in this study is qualitative. This research is a type of evaluation research using a descriptive method. The evaluation design used in this research is the SWOT analysis. The results and conclusions of this study indicate that the management of Pencak silat extracurricular at SMP Negeri 19 Surabaya is good, while SMP Negeri 32 Surabaya cannot be said to be good. Researchers have conducted a more in-depth analysis of the strengths, weaknesses, opportunities, and threats of Pencak silat extracurricular management which includes Planning, Organizing, Implementation, and Supervision of SMP Negeri 19 and SMP Negeri 32 in Surabaya, resulting in a recommendation for SMP Negeri 19 Surabaya and SMP Negeri 32 Surabaya.